Consumer Ethnocentrism, Demographic Characteristics and Willingness to Buy Commercial Banking Services in Kenya - S. M., Maina, (European Scientific Journal, ESJ, 2016)
International marketing empirical literature has indicated the existence and strength of relationships among the consumer ethnocentrism, demographic variables and product attitude vary in different market context. Subsequently consumer ethnocentrism and purchase intentions influence depends on the product categories and other market factors. It is on the basis of this premise that the current study embarked on assessing the moderating effect of demographic characteristics on the relationship between consumer ethnocentrism and willingness to buy banking services. Descriptive and explanatory research design were used in the study. Primary data was collected among 374 commercial banks account holders in Kenya. Data was analyzed using step wise binary logit regression. Consumer national ethnocentrism was found to have a negative influence on the willingness to buy banking services from foreign owned commercial banks. The assessment of the effect of demographic characteristics on willingness to buy commercial banking services revealed that as the levels of respondents’ income per month increased, there was high preference of buying from foreign owned banks and vice versa. However age, gender and income do not moderate the relationship between consumer ethnocentrism and willingness to buy banking services. This indicate the essence of intergroup differentiation in service or market offerings as well as market segmentation and targeting.